The Student’s Learning Outcomes and Scientific Literacy Improvement Through the Implementation of Reading to Learn and Discovery Learning Models - Gadis Yunita Berliana; Sugiyanto Sugiyanto; Indra Fardhani (Postgraduate, University of Mataram, 2023)
This study aimed to determine the effect of the implementation of two learning models, discovery learning and Reading to Learn on scientific literacy skills and student learning outcomes on the excretory system material. This research was conducted in a Junior High School in the city of Malang involving 29 students of 8th grade. This study used pre-experimental research design (one group pretest-posttest design). Data were collected through pretest, posttest, and worksheet questions. Data were analyzed using non-parametric statistical tests (Wilcoxon test), n-gain and d-effect size. The findings revealed that there was an increase in scientific literacy skills and student learning outcomes as indicated by the n gain of 0.58 (upper medium) and 0.77 (high). The use of discovery learning and Reading to Learn models has been shown to have a strong positive/effective impact on improving students' learning outcomes and scientific literacy skills, as shown by the d effect size values of 2.13 and 3.28, which fall into the large effect category